Factors determining the purchase of insurance products - Jańska, Anna; Kędra, Arleta (Czynniki determinujące zakup produktów ubezpieczeniowych, 2019)
This paper centres to the presentation of analyzed potential relations between the determinants of purchasing decisions regarding insurance products and socio-demographic variables, i.e. age, gender, place of residence, income, occupational status, and number of people in the household. The authors also examined whether making financial decisions in a household determines purchasing decisions concerning insurance products. The main hypothesis is: from the perspective of an elderly customer, inherent features of an analyzed insurance product are more vital than aspects regarding the sales process. The analysis was conducted using the ordered logit model, where factors determining purchases of insurance products were used as dependent variables.
Econometrics = Ekonometria, 2019, Vol. 23, No. 1, s. 19-28
Keywords: insurance; ubezpieczenia; ordered logit model; customers preferences; purchase decisions; uporządkowany model logitowy; preferencje klientów; decyzje zakupowe